1993
DOI: 10.1002/j.1460-2075.1993.tb05648.x
|View full text |Cite
|
Sign up to set email alerts
|

The determinants for Sm protein binding to Xenopus U1 and U5 snRNAs are complex and non-identical.

Abstract: The Sm binding sites of different spliceosomal U small nuclear RNAs (snRNAs), the RNA structural elements required for interaction with common snRNP proteins, have been considered to be similar or identical. Here we show that this is not the case. Instead, structural and sequence features unique to U1 or U5 snRNAs that contribute to common protein binding are identified. The determinants of Sm protein binding in both RNAs are complex, consisting in U5 of minimally two and in U1 of minimally four separate struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
67
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 39 publications
3
67
0
Order By: Relevance
“…The secondary structure, but not the sequence, of this stem loop is conserved. Interestingly, deletion of the terminal stem of U1 produced a stable RNA in Xenopus oocytes that was not Sm-precipitable (Jarmolowski and Mattaj 1993), whereas deletion of the terminal stem loop in HeLa extracts altered the sedimentation behavior of the resulting U1 particles (Patton et al 1987). Here, we observed that several phosphates within the terminal stem loop of U1 significantly affect RNP stability when changed to phosphorothioates.…”
Section: A Stem-loop Clamp For the Sm Ringmentioning
confidence: 71%
“…The secondary structure, but not the sequence, of this stem loop is conserved. Interestingly, deletion of the terminal stem of U1 produced a stable RNA in Xenopus oocytes that was not Sm-precipitable (Jarmolowski and Mattaj 1993), whereas deletion of the terminal stem loop in HeLa extracts altered the sedimentation behavior of the resulting U1 particles (Patton et al 1987). Here, we observed that several phosphates within the terminal stem loop of U1 significantly affect RNP stability when changed to phosphorothioates.…”
Section: A Stem-loop Clamp For the Sm Ringmentioning
confidence: 71%
“…In agreement with this finding, a subset of the U5 nucleotides implicated in the 5' splice site-U5 interaction have been cross-linked to exonic and intronic RNA sequences near the 5' splice site, indicating a close, physical juxtaposition of U5 and 5' splice site nucleotides during splicing (41, 44). Taken together, these studies suggest that the U5 snRNA plays an active role in the function of this snRNP.Aside from the few nucleotides implicated in the exon-U5 interaction, only the conserved Sm core protein binding site of U5 has a defined function (13,14,21 functional significance. An important first step towards this goal is the determination of U5 secondary structure, which is most effectively accomplished through phylogenetic analysis; this approach delineates structures that are presumed, by their evolutionary conservation, to be functionally significant (27).…”
mentioning
confidence: 83%
“…Aside from the few nucleotides implicated in the exon-U5 interaction, only the conserved Sm core protein binding site of U5 has a defined function (13,14,21 functional significance. An important first step towards this goal is the determination of U5 secondary structure, which is most effectively accomplished through phylogenetic analysis; this approach delineates structures that are presumed, by their evolutionary conservation, to be functionally significant (27).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical modification studies of nematode SL RNA indicate a functional role in trans-splicing for purines in the upstream but not the downstream stem-loop (Hannon et al 1992), however, the SL RNA of Schistosoma does not contain a similar upstream stem-loop (Rajkovic et al 1990). Stem-loops may quantitatively facilitate Sm protein binding to U snRNAs (Jarmalowski and Mattaj 1993;Hinz et al 1996) but they are not essential (Raker et al 1999). As Figure 6 shows, the 46-nucleotide Ciona SL RNA is more like the relatively simple SL RNA of Schistosoma than the more complex classical SL RNA secondary structure represented by Caenorhabditis SL1.…”
Section: Trans-splicing Of Tni/␤-gal Chimeric Transcriptsmentioning
confidence: 99%